Influence of ozonised irrigation water on the morphological, bacteriological and sensory characteristics of ‘Saint-Pierre’ tomatoes grown in Algeria - Fouzia BENALI; Nadia RAMDANI (Acta Agriculturae Slovenica)
This article focuses on the study of the influence of ozonised water irrigation on the morphological, bacteriological and sensory characteristics of ‘Saint-Pierre’ tomatoes grown in Algeria. The results were compared with those irrigated with non-ozonised tap water called control of the same varietal type and grown under the same conditions. The work was carried out on seedlings of tomatoes grown and irrigated with ozonised water at different ozonisation times: 10- seconds, 20- seconds and 30-seconds, corresponding to lot I (tomato at 10-s), lot II (tomato at 20-s) and lot III (tomato at 30-s), respectively. Irrigation with ozonised water does not cause defects in shape, skin or colour of the fruits. They are, distinguished by a round shape, very red in colour, consistent and slightly acidic in taste. With good microbiological stability in accordance with the standard and good organoleptic quality except for the taste character of tomatoes at 30-seconds where a majority of evaluators estimated that ‘they were bland and no big difference for the other criteria analysed. In general, our results showed that the ozonisation of irrigation water improves the growth, development, vigour and yield of tomato plants without altering the marketability of the fruits. This process encourages the use of ozonised water in agriculture since it has a high added value from an environmental and economic point of view and it can be generalized to other crops.